Transforming engineering communication - Lloyd, Natalie; Ramiah, R. (2014)
'Engineers do not need to know how to write'. This statement expresses a common belief amongst engineering undergraduate students, which is often compounded by a resistance to communication practice. This attitude is contrary to engineering industry and Engineers Australia expectations, which value communication and rate written communication as a key competency required for engineers (Male et al., 2011). Whilst communication skills form an important part of engineering curricula, some engineering faculty members express the view that it is not their role to teach language and communication skills. The responsibility for the development of these skills is often passed on to the language specialists or the University's Learning Centres. However, communicating technological information involves interpreting and using specialised disciplinary discourse. Therefore, engineering discipline lecturers have a key role to play in teaching their students disciplinary discourse (Airey, 2011). This paper is an exploration of the realities of integrating language instruction by a Civil Engineering discipline lecturer in a core second year unit. An important aspect of the research is students' resistance to the integration efforts, which was primarily due to their expectations of purely technical content for the unit. Another interesting aspect was the resistance to the change in the pedagogical approach taken to integrate language and communication all skills. This paper will question/problematise this resistance to better understand how integration efforts can move forward.